The Influence of Product Quality on Purchase Interest in Halal Cosmetics - Didit Darmawan; Ayu Mubarokatum Maulidah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Cosmetics or make-up are care products used to beautify appearance or enhance body fragrance, with the procedure for their use known as makeup application. This study aims to examine the impact of product quality on interest in purchasing halal cosmetics using a qualitative approach with a literature review method. Data were collected from various academic sources discussing the relationship between product quality and consumer interest in purchasing halal cosmetics. Descriptive analysis was conducted to identify patterns of findings and draw conclusions based on relevant academic literature. The results of the study indicate that the quality of halal products significantly affects consumer purchasing interest, which is assessed not only in terms of effectiveness and durability, but also compliance with halal standards. These findings confirm that product quality is a major factor in building consumer trust, value perception, and loyalty. Therefore, manufacturers are advised to maintain consistent quality, effectiveness, and halal compliance, supported by halal regulations and certification, in order to increase competitiveness and create a competitive advantage in the market.